The Accounting Information System Design: Cash Inflow at Islamic Boarding School - Dwi Sulistiani; Wahidmurni (Politeknik Negeri Madiun, 2022)
This qualitative research aims to determine how the design of the cash inflow of the accounting information system (AIS) in Sabilurrosyad Islamic boarding school in Malang. Semi-structured interviews, FGD and documents were used to answer the research question. It was found that the control environment, risk understanding, information and communication and monitoring in this boarding school were still not good. The design of the AIS of cash inflow is done by drafting the cash receipt form, which is the internal evidence needed to support external evidence. Evidence of the first note is also designed in the form of a cash book that is written manually at each cash-in transaction. Flowchart design consists of a flowchart procedure for receiving donations, payment of SPP instalments and payment of building instalments. The recommendation for the Sabilurrosyad boarding school is that the transactions that occur can be clarified and recorded in an orderly manner in the forms and records that exist. There is a separation of duties between the cashier and the accounting department as well as the purchasing and warehouse parts. The organizational and control activities need to be improved with the approval of school principals for non-routine expenditures.